Evaluasi dan Perancangan Model Bisnis Usulan NYFORU Menggunakan Business Model Canvas - Putri, Afina Nafisah; Hasun, Farda; Pulungan, Muhammad Almaududi (Metode : Jurnal Teknik Industri, 2025)
NYFORU is a business that focuses on fan collections and K-pop merchandise at affordable prices since 2020. Products offered include sticker collection, keychain collection, phone case and griptok collection, and photocard holder collection. In the last three years, turnover has decreased, with 2023 revenue of Rp. 96,967,463, down 33.4% from 2022. The causes are limited human resources, lack of product variety, and not optimal promotion. To overcome this, a business model design and evaluation using Business Model Canvas was conducted. Data were obtained through interviews, observations, and literature studies, then analyzed using SWOT. The results showed three priority improvement blocks: customer segment, value propositions, and channels. Proposed improvements include Shopee export, adding artist variations, and strengthening channel X. Financial simulations show that this business model change is feasible.